Alcohol evaluations and acceptability: Examining descriptive and injunctive norms among heavy drinkers. (March 2015) - Foster, Dawn W.; Neighbors, Clayton; Krieger, Heather
Abstract: Objectives: This study assessed descriptive and injunctive norms, evaluations of alcohol consequences, and acceptability of drinking. Methods: Participants were 248 heavy-drinking undergraduates (81.05% female; Mage  = 23.45). Results: Stronger perceptions of descriptive and injunctive norms for drinking and more positive evaluations of alcohol consequences were positively associated with drinking and the number of drinks considered acceptable. Descriptive and injunctive norms interacted, indicating that injunctive norms were linked with number of acceptable drinks among those with higher descriptive norms. Descriptive norms and evaluations of consequences interacted, indicating that descriptive norms were positively linked with number of acceptable drinks among those with negative evaluations of consequences; however, among those with positive evaluations of consequences, descriptive norms were negatively associated with number of acceptable drinks. Injunctive norms and evaluations of consequences interacted, indicating that injunctive norms were positively associated with number of acceptable drinks, particularly among those with positive evaluations of consequences. A three-way interaction emerged between injunctive and descriptive norms and evaluations of consequences, suggesting that injunctive norms and the number of acceptable drinks were positively associated more strongly among those with negative versus positive evaluations of consequences. Those with higher acceptable drinks also had positive evaluations of consequences and were high in injunctive norms. Conclusions: Findings supported hypotheses that norms and evaluations of alcohol consequences would interact with respect to drinking and acceptance of drinking. These examinations have practical utility and may inform development and implementation of interventions and programs targeting alcohol misuse among heavy drinking undergraduates. Highlights: Consequence evaluations and descriptive norms are uniquely associated with drinking Evaluations, descriptive, and injunctive norms also associate with approval of drinking Injunctive norms associate with approval for high descriptive norms and evaluations